A Solid-State Fluorescence Switch Based on Triphenylethene-Functionalized Dithienylethene With Aggregation-Induced Emission - Zhang, Haining; Hu, Xiaoxiao; Zhu, Huijuan; Shen, Limin; Liu, Congmin; Zhang, Xiaoman; Gao, Xinyu; Li, Lingmei; Zhu, Yan-Ping; Li, Ziyong (Frontiers in Chemistry, 2021)
The development of novel dithienylethene-based fluorescence switches in the aggregated state, and the solid state is highly desirable for potential application in the fields of optoelectronics and photopharmacology. In this contribution, three novel triphenylethene-functionalized dithienylethenes (1–3) have been designed and prepared by appending triphenylethene moieties at one end of dithienylethene unit. Their chemical structures are confirmed by 1H NMR, 13C NMR, and HRMS (ESI). They display good photochromic behaviors with excellent fatigue resistance upon irradiation with UV or visible light in Tetrahydrofuran (THF) solution. Before irradiation with UV light, they exhibit Aggregation Induced Emission (AIE) properties and luminescence behaviors in the solid state. Moreover, upon alternating irradiation with UV/visible light, they display effective fluorescent switching behaviors in the aggregated state and the solid state. The experimental results have been validated by the Density Functional Theory (DFT) calculations. Thus, they can be utilized as novel fluorescence switches integrated in smart, solid-state optoelectronic materials and photopharmacology.